Towards strategic partnership: Philippines-Japan relations after seventy years - Trinidad, Dennis D. (Animo Repository, 2018)
From adversaries during World War II to strategic partners in the twenty-first century, the relationship between the Philippines and Japan has grown by leaps and bounds in the last seventy years. Over time, the two countries’ economies have become interdependent and leaders from both sides mutually acknowledge the strategic importance of each other’s security and prosperity. Of course, there have been challenges as well such as evolving power dynamics and some episodes of exploitation by Japan in the past. Nonetheless, both sides have chosen to go forward and allowed their relations to be guided by pragmatism. This chapter attempts to provide a succinct discussion of domestic and international factors that transformed Philippines-Japan relations to what it is today. It argues that both sides desire to make security and defense cooperation a main feature of their twenty-first century strategic partnership. This trajectory is explained by confluence of internal and external factors including the emergence of right-of-center politics and institutional reforms in Japan, new regional security environment, uncertainty of U.S. commitment, and domestic politics in the Philippines. © 2018 selection and editorial matter, Mark R. Thompson and Eric Vincent C. Batalla; individual chapters, the contributors.